Effect of melatonin on gut microbiome and metabolomics in diabetic cognitive impairment - Gao, Ming; Li, Jie; Han, Xu; Zhang, Beiyao; Chen, Jinting; Lang, Jiadong; Zhang, Qiangqiang (Frontiers in Pharmacology, 2024)
Diabetic cognitive impairment(DCI) presents as a central nervous complication of diabetes especially among aging population. Melatonin (MEL) is known for its antioxidant and anti-inflammation effects in neuroprotective aspects. Recent evidence has demonstrated that the gut microbiome plays a key role in DCI by modulating cognitive function through the gut–brain crosstalk. MEL has been shown to modulate gut microbiota composition in diabetic model. However, the underlying mechanism through which the gut microbiome contributes to DCI remains unclear. This study aims to investigate the effect and mechanism of MEL in attenuating DCI in relation to regulating the gut microbiome and metabolomics. Cognitive and memory function were assessed by the Morris water maze test, histopathological assessment of brain tissues, and immunoblotting of neuroinflammation and apoptosis. The levels of serum tumor necrosis factor-α (TNF-α) and Interleukin-18 (IL-18) were measured by enzyme-linked immunoassays to reflect the circulatory inflammation level.16S rRNA microbiome sequencing analysis was performed on control mice(db-m group), diabetic mice(db-db group) and MEL-treated diabetic mice(db-dbMEL group). Gut metabolites changes were characterized using liquid chromatography tandem mass spectrometry (LC-MS/MS). Our study confirmed that MEL alleviated diabetes-induced cognition and memory dysfunction. MEL protected against neuroinflammation and apoptosis in hippocampus of db-db mice. MEL corrected the increased abundance of Bacteroides and Dorea and the reduced abundance of Prevotella in db-db mice. The vast majority of differential metabolites among the three groups were lipids and lipid-like molecules. MEL significantly restored the reduced levels of pyruvate and lactic acid. Our results supported the use of MEL as a promising therapeutic agent for DCI, in which the underlying mechanism may be associated with gut microbiome and metabolomics regulation.